An analysis of disparities in imaging for suspected traumatic brain injury among patient visits to emergency departments (2010–2021) - Misciagno, Susan Avila; Dancy, Erin; Jiroutek, Michael R.; Holland, Melissa A. (Frontiers in Neurology, 2025)
BackgroundTraumatic brain injuries (TBI) are an increasing global public health concern. Current guidelines for neuroimaging lack sufficient evidence on specific recommendations for conducting diagnostic imaging during emergency department (ED) visits for TBI. Moreover, imaging underutilization and healthcare disparities persist despite evidence that early access to imaging can significantly impact the prediction of functional outcomes in patients presenting with suspected TBI. Therefore, investigating neuroimaging utilization nationwide for patient screening amongst those who present to the ED for TBI is crucial.MethodsThis retrospective, observational, cross-sectional study was conducted using data from the National Hospital Ambulatory Medical Care Survey (NHAMCS), an annual, nationally representative sample survey of visits to hospital EDs in the United States, conducted by the National Center for Health Statistics. A multivariable logistic regression model was constructed to evaluate predictors of interest available in the database on the use of imaging for visits to the ED with a suspected TBI. A graph of the annual percentage of ED visits at which imaging was used was constructed.ResultsVisits by the Black race group compared to the White race group, by those 0–17 years, 18–39 years, and 40–64 years compared to those 65+, by females compared to males, and visits using Medicaid/SCHIP/CHIP compared to visits using private insurance all had lower odds of receiving imaging. Further, visits in the West and Northeast, as compared to the South and those in rural areas as compared to urban areas, had lower odds of receiving imaging. Visits by individuals with more chronic conditions were found to have higher odds of receiving imaging. After bottoming in 2014, imaging use increased.ConclusionDisparities in the use of imaging for ED patients with a suspected TBI persist. Ongoing public health education efforts are needed to ensure proper screening during ED visits with a suspected TBI and for care post-TBI.